Basement Characteristics In The Lower Magdalena Valley and The Sinú And San Jacinto fold belts: evidence of a Late Cretaceous Magmatic Arc at the South of The Colombian Caribbean - Silva-Arias, Alejandro; Páez-Acuña, Liliana-Andrea; Rincón-Martínez, Daniel; Tamara-Guevara, Javier-Alfonso; Gomez-Gutiérrez, Pedro-David; López-Ramos, Eduardo; Restrepo-Acevedo, Sandra-Milena; Mantilla-Figueroa, Luis-Carlos; Valencia, Victor (CT&F - Ciencia, Tecnología y Futuro, 2016)
The onset of subduction in the Caribbean Plate under the South American Plate allowed the development of an Active Continental Margin; the age of onset, the mechanism, and the plates involved are a discussion topic, especially at the Colombian South Caribbean Margin, due to the lack of geological information related to the basement. This article in tegrates petrographic, geochemical analyses and U/Pb dating of basement samples, in addition to the inclusion of published magnetic anomalies maps from the North of Colombia, in order to generate a compositional distribution map of the basement and determine the presence of a magmatic arc under the sediments of the Lower Magdalena Valley (LMV), which supports the existence of a Late Cretaceous active continental margin represented by a magmatic arc, called Magmatic Arc of Magangué. Dating of the arc yield a Late Cretaceous Age (84-74 Myr), and petrographic and geochemical evidence suggests it is comprised of igneous bodies of felsic to intermediate composition, which intrudes the LMV continental crust originated in a subduction setting. The origin of the LMV continental crust seems to be related to the continent-continent collision (consolidation of Pangaea) during the Permian (300 Ma ago), and to the post-Alleganian extension event of Triassic age (232 Ma ago).